Nanoscale sensing using point defects in single-crystal diamond: Recent progress on nitrogen vacancy center-based sensors - Bernardi, Ettore; Nelz, Richard; Sonusen, Selda; Neu, Elke (Crystals, 2017)
Individual, luminescent point defects in solids, so-called color centers, are atomic-sized quantum systems enabling sensing and imaging with nanoscale spatial resolution. In this overview, we introduce nanoscale sensing based on individual nitrogen vacancy (NV) centers in diamond. We discuss two central challenges of the ﬁeld: ﬁrst, the creation of highly-coherent, shallow NV centers less than 10 nm below the surface of a single-crystal diamond, second, the fabrication of tip-like photonic nanostructures that enable efﬁcient ﬂuorescence collection and can be used for scanning probe imaging based on color centers with nanoscale resolution.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Color center; Diamond; Magnetic sensing; Nanostructures; Scanning probes